Upaya Peningkatan Pengetahuan Ibu Hamil Dalam Pencegahan Stunting Pada Masa Kehamilan Di Klinik Pratama Kabupaten Ponorogo: Upaya Peningkatan Pengetahuan Ibu Hamil Dalam Pencegahan Stunting Pada Masa Kehamilan Di Klinik Pratama Kabupaten Ponorogo - Ocha, Fifi Arisanti (MUJAHADA: Jurnal Pengabdian Masyarakat, 2024)
The nutritional status and health of mothers and children greatly determine the quality of human resources. The pre-pregnancy period, pregnancy period, and breastfeeding period are very critical periods in determining the quality of nutrition and maternal health. Providing health education through health promotion aids, such as visual aids, hearing aids, and audio-visual aids, is an important step in increasing the knowledge of pregnant women. Audiovisual media is considered more effective in learning because it can provide a more immersive real experience compared to audio or visual media alone. The community service activities carried out aim to increase the knowledge of pregnant women about the importance of stunting prevention during pregnancy. This activity began with the provision of a pre-test questionnaire to measure the level of initial knowledge of pregnant women. Furthermore, health education is carried out using audiovisual media (video). After the education session, a post-test questionnaire was given to evaluate the increase in knowledge. The results of this activity showed that the average knowledge score of pregnant women before education was 68. After being given education, the average score increased to 85.86, which means there was an increase of 26% or a difference of 17.86 points. The results of statistical analysis showed that the value of ρ-value = 0.000 (ρ-value < 0.05), which means that there was a significant difference in scores between before and after health education using audiovisual media. Thus, it can be concluded that there is a significant increase in knowledge about stunting prevention during pregnancy after being given health education using audiovisual media (video) to pregnant women at the Primary Clinic of Ponorogo Regency.